Therapeutic Misconception about Research Procedures: Does a Simple Information Chart Improve Understanding?. Issue 2 (26th February 2022) - Campbell, Gavin; Dixon, Margie D.; Lohani, Minisha; Cook, John; Hianik, Rachel; Thomson, Mary Catherine; Abernethy, Eli; Lewis, Colleen; Switchenko, Jeffrey; Harvey, R. Donald; Pentz, Rebecca D.
ABSTRACT: In phase I trials, some biospecimens are used both for research and patient care and some for research only. Some research participants have therapeutic misconception, assuming all biospecimens are for patient care. This study's aim was to test if a simple information chart would improve understanding of nontherapeutic research procedures. A two‐arm study was conducted. Participants in the control group (C) were asked whether biospecimens were for their care, for research only, or for both. The experimental group (E) was asked the same questions but provided with a study‐specific information chart labeling the purpose of each biospecimen. One hundred one patients were interviewed. In both arms, understanding that pretreatment blood draws were for patient care and research was moderate (49% for C and 62% for E). Understanding that posttreatment blood draws were for research only was significantly higher in the experimental arm (16% for C and 44% for E; p = 0.002). Providing a simple information chart may help alleviate this aspect of therapeutic misconception.